Materials and methods of analysis for the study of the Ainu language - Southern Hokkaidō and Sakhalin varieties - Elia Dal Corso (Edizioni Ca' Foscari, 2022)
This volume is intended to be a practical manual to learn the basics of the Ainu language, in its varieties of Southern Hokkaidō and Sakhalin. Each lesson presents one specific topic that is investigated taking into account both varieties of the language. Three kinds of activities guide the student throughout each lesson to inductively make generalizations on the language that can be supported by linguistic evidence and, possibly, to revise the information they were given as a start of their analysis. In order to do this, the student learns to observe the data, recognize recurring patterns and exceptions, and formulate a description of the language behaviors illustrated by the given examples. At the end of each lesson the student actively gains knowledge of the Ainu language by producing themselves a set of descriptive rules. The course aims at giving the student some basic analytical tools to approach and analyze Ainu language sources. Furthermore, the student will gain knowledge about the genealogical relationship of the Ainu language and about important sociolinguistic issues relative to its past history and present status of vitality.